CTCFL (BORIS) mRNA Expression in a Peripheral Giant Cell Granuloma of the Oral Cavity - Graciela Zambrano-Galván; Miguel Reyes-Romero; Ronell Bologna-Molina; Oscar Eduardo Almeda-Ojeda; Obed Lemus-Rojero (Hindawi Limited, 2014)
Peripheral giant cell granuloma (PGCG) is a relatively common benign reactive lesion of the oral cavity which can occur at any age. CTCFL/BORIS (CTCF like/Brother of the Regulator of Imprinted Sites) and CTCF (CCCTC-binding factor) are paralogous genes with an important role in the regulation of gene expression, genomic imprinting, and nuclear chromatin insulators regulation. BORIS expression promotes cell immortalization and growth while CTCF has tumor suppressor activity; the expression pattern may reflect the reverse transcription silencing of BORIS. The aim of this work was to describe a histopathological and molecular approach of an 8-year-old pediatric male patient with PGCG diagnosis. It was observed that the PGCG under study expressed CTCF as well as BORIS mRNAs alongside with the housekeeping gene GAPDH, which may be related to possible genetic and epigenetic changes in normal cells of oral cavity.